8- Coverage of African Related Studies in International Journals: Greater Exposure for ‘Public Intellectuals’ in Sociology and Industrial Relations? - Wood, Geoffrey; Dibben, Pauline (African Sociological Review, 2006)
This paper assesses the coverage of African topics in leading international journals, focussing on sociology and an important sub-discipline, industrial relations. In doing so, it evaluates whether the number of articles with an African focus has grown or declined over the last decade. The findings reveal a very limited exposure of African and related debates. Moreover, the number appears to be declining, with periodic bulges in publication activity linked to journal special issues. However, there appears to be no relationship between the ranking of journals and the appearance of articles on African issues; scholars working on Africa have published in the most highly ranked journals in the field. There are therefore some grounds for optimism. But for African scholars, this is heavily dependent on the availability of resources. Without such resources, some doubt is cast on the future ability of ‘public intellectuals’ in Africa to influence international debates.